Economic Growth and Political Integration: Estimating the Benefits from Membership in the European Union Using the Synthetic Counterfactuals Method - Nauro F. Campos; Fabrizio Coricelli; Luigi Moretti (Institute for the Study of Labor (IZA), 2014)
This paper presents new estimates of the economic benefits from economic and political integration. Using the synthetic counterfactuals method, we estimate how GDP per capita and labour productivity would have behaved for the countries that joined the European Union (EU) in the 1973, 1980s, 1995 and 2004 enlargements, if those countries had not joined the EU. We find large positive effects from EU membership but these differ across countries and over time (they are only negative for Greece). We calculate that without deep economic and political integration, per capita incomes would have been, on average, approximately 12 percent lower.
Keywords: C33; F15; F43; O52; 330; economic growth; European Union; synthetic counterfactuals